Blockchain Approach As A Digital Identity Security Solution In Banking Digital Transformation - Umar Al Faruq Siregar Al Faruq Siregar; Yessi Claudia Sitepu; Mawar Adelia Br Marpaung; Samuel Rizky Ananda Sitindaon; Fadly Robbani Tua Lumban Tobing; Sudarto Sudarto (Jurnal Media Computer Science, 2026)
Digital transformation in the banking sector requires stronger security in managing customers’ digital identities. Conventional centralized systems remain vulnerable to data breaches, identity fraud, and cyberattacks, highlighting the need for a more secure and decentralized approach. This study aims to examine the use of blockchain technology as an alternative solution to enhance digital identity security in digital banking systems using the Systematic Literature Review (SLR) method. This approach involves selecting and analyzing relevant scholarly articles to identify trends, challenges, and the effectiveness of blockchain implementation. The findings indicate that blockchain can improve the reliability and accuracy of digital identity data through cryptographic mechanisms, decentralized systems, and verification processes that do not rely on third parties. In addition, the use of smart contracts and Decentralized Identifiers (DID) strengthens authentication processes and reduces the risk of fraud. Therefore, blockchain has the potential to become a key foundation for building a secure, transparent, and trustworthy digital banking ecosystem, although clear regulations and adequate infrastructure readiness are still required for optimal implementation.